POWER SYSTEMS RESILIENCE ENHANCEMENT: A REVIEW OF OPERATIONAL ENHANCEMENT APPROACHES (The Proceedings of The International Conference on Climate Change, 2023)
Power system resilience enhancement (PSRE) describes approaches used in reducing the extent of direct impacts caused by climate change and approaches in quickly restoring the grid functionality to its usual status. Recently, much research has been conducted on PSRE approaches to the effects of climate change. There are abundant review papers on PSRE to the impacts of climate. But there are no significant amounts of review papers focusing on operational resilience enhancement approaches on the entire power system, particularly with the focus and classifications suggested in this paper. Operational resilience-oriented modelling approaches and strategies have been comprehensively reviewed across five distinct dimensions including operational strategy, enhancement type, hierarchy, modelling methods and model formulation. A standard literature review process was followed to identify articles, with the initial search covering PSRE in general. Out of these, papers focusing on operational resilience enhancement were selected. The selected papers were classified according to the operational enhancement approaches, enhancement types, modelling methods, model formulation and the enhanced hierarchy criteria. The operational approaches, which include distributed energy resources, microgrids, preventive control, response, design standards upgrade, advanced visualisation and situational awareness systems and advanced and adaptive restoration operational techniques, were reviewed.  The study reveals that for a single operational approach, different enhancement techniques can be employed using different modelling techniques. However, limited studies have so far explored an entire grid improvement as opposed to transmission and distribution structures. In addition, among the optimisation, probabilistic, simulation and AI based modelling methods, optimisation approaches have been extensively used. There are very limited studies that combine these modelling approaches in one study. Research gaps and directions for future research have been suggested in this paper.
Keywords: operational measures; resilience; climate change; extreme weather; power systems resilience enhancement; modelling